1989
DOI: 10.1017/s0950268800029988
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial contamination of stored water and stored food: a potential source of diarrhoeal disease in West Africa

Abstract: The food and water hygiene in two Liberian communities was studied in a house-to-house diarrhoea survey. The level of contamination with enterobacteria of drinking water stored in the households was significantly higher than at the water sources. Food hygiene standards were low, particularly in the urban slum where storage of cooked food for long periods led to bacterial multiplication at high levels. Infant foods were particularly heavily contaminated. It is concluded that when water supply programmes are pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 3 publications
1
24
0
Order By: Relevance
“…The main risk of filter systems is through increased handling and storage of water within the household, and past studies have shown that household storage and handling is a significant source of contamination, perhaps the major source (Molbak et al 1989). This assumption is supported by a field study evaluating arsenic removal systems in Bangladesh, which found that such systems had higher levels of microbial contamination in the filtrated water than in the tube wells from which the water was taken (Sutherland et al 2002) and may therefore increase the risk of water-related infectious disease.…”
Section: Article | Effect Of Arsenic Interventions On Disease Burdenmentioning
confidence: 99%
“…The main risk of filter systems is through increased handling and storage of water within the household, and past studies have shown that household storage and handling is a significant source of contamination, perhaps the major source (Molbak et al 1989). This assumption is supported by a field study evaluating arsenic removal systems in Bangladesh, which found that such systems had higher levels of microbial contamination in the filtrated water than in the tube wells from which the water was taken (Sutherland et al 2002) and may therefore increase the risk of water-related infectious disease.…”
Section: Article | Effect Of Arsenic Interventions On Disease Burdenmentioning
confidence: 99%
“…[16][17][18][19] Publicly available data on water quality in Monrovia, which has a history of cholera outbreaks, have been restricted to studies of the informal settlement of West Point. [20][21][22][23] Both cities have planned or ongoing investments in municipal water infrastructure. In Port Harcourt, the Urban Water Sector Reform and Port Harcourt Water Supply and Sanitation Project and Urban Water Sector Reform Projects (2014-2019) include support from the African Development Bank and the World Bank to rehabilitate and expand the public piped water supply and construct sanitation infrastructure.…”
Section: Introductionmentioning
confidence: 99%
“…Women used to carry it on their backs to fetch and keep water from spring, to prepare and keep foods, to keep leftovers fresher [2]. Despite its importance, food spoilage is the major drawback which limits its use in African rural area [3]. One of the most promising innovations in food packaging is the use of nanotechnology to develop antimicrobial packaging [4].…”
Section: Introductionmentioning
confidence: 99%